2008
DOI: 10.1007/s12155-008-9022-x
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Fuel Crops Research for Energy Security and Rural Development in Developing Countries

Abstract: Soaring prices of fossil fuels, geo-political issues and environmental pollution associated with fossil fuel use has led to worldwide interest in the production and use of bio-fuels. Both the developed and developing countries have developed a range of policies to encourage production of combustible fuels from plants that triggered public and private investments in bio-fuel crop research and development, and bio-fuels production. In this article, we discuss the potential benefits of bio-fuels in increasing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 20 publications
2
56
0
Order By: Relevance
“…Ethanol feedstock CSH 22SS, the first sweet sorghum hybrid released in India, was based on the ICRISAT-bred female parent ICSA 38. Strategic research at Indian national program and ICRISAT indicated that ethanol production in Indiausing sweet sorghum is cost-effective and its cultivation gives 23% additional income to farmers compared to the grain sorghum [50]. There are minimal food-fuel tradeoffs in sweet sorghum but season-specificity exists.…”
Section: Sweet Sorghum For Ethanol Andanimal Feedmentioning
confidence: 99%
“…Ethanol feedstock CSH 22SS, the first sweet sorghum hybrid released in India, was based on the ICRISAT-bred female parent ICSA 38. Strategic research at Indian national program and ICRISAT indicated that ethanol production in Indiausing sweet sorghum is cost-effective and its cultivation gives 23% additional income to farmers compared to the grain sorghum [50]. There are minimal food-fuel tradeoffs in sweet sorghum but season-specificity exists.…”
Section: Sweet Sorghum For Ethanol Andanimal Feedmentioning
confidence: 99%
“…Like grain sorghum, sweet sorghum, a warm-season crop, can be cultivated by smallholder farmers in rainfed areas. The crop can be grown successfully on clay, clay loam or sandy loam soils and can tolerate salinity and alkalinity to a large extent (Reddy et al, 2008, Rao et al, 2009). …”
Section: Sweet Sorghum For Ethanol Productionmentioning
confidence: 99%
“…It is a well-known fact that sweet sorghum has the ability to adapt to drought, saline and alkaline soils and water logging conditions (Reddy et al, 2008, Rao et al, 2009). Besides, a shorter growing period of four months, it has a low water requirement as compared to sugarcane (Soltani et al, 1994 and familiarity of farmers in cultivation of sorghum makes it much easier and willingness to grow sweet sorghum.…”
Section: Potential Benefits Of Sweet Sorghum As Feedstock For Ethanolmentioning
confidence: 99%
“…Management system reforms for water supply projects need to be intensified, and improvements in long-term project operations and socialized services should be made. Moreover, strengthening the protection of water resources, assuring water quality, improving the living conditions and environment of rural residents, and increasing residents' health levels are also important in narrowing the gap between urban and rural areas and promoting the common development of the whole society [8].…”
Section: Introductionmentioning
confidence: 99%